From ultraviolet-B to red photons: Effects of end-of-production supplemental light on anthocyanins, phenolics, ascorbic acid, and biomass production in red leaf lettuce - Yilin Zhu; Bhimanagouda S. Patil; Shuyang Zhen (PLoS ONE, 2025)
Plants possess an array of photoreceptors, such as UVR8, cryptochromes, and phytochromes, that perceive the spectral quality of light and regulate plant morphology, growth, and physiology. The use of light-emitting diodes enables the application of targeted light spectra to elicit specific plant responses during cultivation. However, there is a lack of comparative studies evaluating the effects of different spectral regions within the same crop. We comprehensively quantified how various light spectra, ranging from ultraviolet-B to red, affect plant growth and the accumulation of beneficial phytochemicals, including anthocyanins, phenolics, and ascorbic acid, in red leaf lettuce (Lactuca sativa) cv. Red Salad Bowl and Rouxai. Plants were grown under a background white LED light of 200 µmol m-2 s-1 for 16 hours per day (control), and supplemented with red (peak at 659 nm), blue (444 nm), violet (404 nm), ultraviolet-A (UVA; 368 nm) radiation at 60 µmol m-2 s-1, or ultraviolet-B (UVB; 309 nm) radiation at 3 µmol m-2 s-1 during the last 7 days of a 28-day production period (end-of-production stage, EOP). For both lettuce cultivars, red, blue and UVB treatments significantly enhanced leaf anthocyanin content compared to the control, with UVB being the most effective despite its low application dosage, followed by the blue and red light treatments. UVB radiation significantly increased total phenolic content in both cultivars (by 80%–99.1% compared to the control), while blue light treatment increased total phenolics by 31.4% in ‘Red Salad Bowl’ only. However, supplemental UVB radiation did not affect total ascorbic acid in either cultivar; the other EOP treatments (red to UVA) increased total ascorbic acid by 19%–35% in ‘Red Salad Bowl’ but had no significant effects in ‘Rouxai’. Notably, crop yield under the UVB treatment was the lowest in both cultivars, with 8.9%–49% lower shoot fresh weight compared to other treatments. In contrast, the violet light treatment resulted in the highest leaf area and shoot biomass in both lettuce cultivars, although it was not effective in enhancing anthocyanins and total phenolics. Our result indicated that there is often a tradeoff between nutritional quality and crop yield, and specific light spectra can be strategically used to enhance nutritional quality or biomass. Low-intensity UVB was the most effective at maximizing anthocyanins and total phenolics, followed by blue light, while supplemental violet light most significantly enhanced lettuce leaf expansion and biomass compared to other light spectra.